Kompetensi Pengadilan Negeri Dalam Pemutusan Sengketa Pemilihan Umum Di Indonesia - Artana, I Putu Juni; Prasetyo, Boedi (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This study examines the competence of the district court in resolving election disputes based on the Central Jakarta District Court Decision Number 757/Pdt.G/2022/PN Jkt Pst, which granted the People's Justice and Prosperity Party (PRIMA)'s lawsuit against the General Elections Commission (KPU) and ordered the suspension of the election stages. The lawsuit was constructed as an unlawful act (PMH), thus the District Court declared itself authorized to adjudicate the case. However, the KPU's actions in verifying political party administration constitute public legal action and fall within the scope of state administrative disputes. Based on Law No. 7 of 2017 concerning Elections, resolving disputes over election processes and decisions falls under the authority of the Elections Supervisory Agency (Bawaslu) and the State Administrative Court (PTUN), while disputes over election results fall under the jurisdiction of the Constitutional Court. This District Court decision demonstrates a conflict of jurisdiction and ignores the principle of lex specialis derogat legi generali.